Аналіз основних факторів, що визначають аерогідродинамічний опір у високошвидкісних зубчастих передачах - Ставицький, В. В.; Носко, П. Л.; Марченко, Д. М.; Філь, П. В.; Кравченко, В. М. (НТУ "ХПІ", 2015)
У статті виявлено природу аерогідродинамічного опору обертанню зубчастих коліс та запропоно- вано прості аналітичні вирази, які надають можливість визначати енергетичну ефективність високошвидкісних зубчастих передач. На підставі рівняння масового балансу визначена щільність оливоповітряної суміші в западинах зубчастого колеса та встановлено число Ейлера, що визначає досягнення її критичного значення. Визначено межі впливу торцевих зазорів на втрати потужності та ефективності застосування змащування зануренням.

This paper presents a discussion of the nature of windage and churning power losses. Relatively straightforward analytical mathematical expressions are offered to determine the energy efficiency of highspeed gears. A series of formulas which enable accurate prediction of windage and churning power losses for one pinion characteristic of gear transmission geometry and prediction of physical properties of lubrication are presented. Presented dependencies allow to calculate energy efficiencies of high-speed gears with minimum calculation efforts not only taking into an account mechanical friction losses, but also taking into account windage and churning power losses. Specific gravities for different kinds of power losses are presented. Analytical dependencies of oil-air density on gear transmission geometries (rotational speed, tooth face width, radial and axial clearances, helix angle) are obtained based on mass balance. Influence limits are studied for the effect of the end gaps on the power losses, and for the effectiveness of lubrication by immersion in an oil bath.
Analysis of key factors that influence aerodynamic friction in high-speed gear transmissions
Keywords: машинобудування; зубчасте колесо; втрати потужності; оливоповітряна суміш; торцевий зазор; high-speed; transmissions; oil-air mixture; tooth face width; axial clearance